Agrarreform und ländliche Abwanderung im Irak - Sozialer Wandel und wirtschaftliche Dynamik in einer sozialistischen Gesellschaft mit Freiräumen für Privatinitiative - Wirth, Eugen (ERDKUNDE, 1982)
In perspective the agrarian reform in Iraq can be subdivided into three periods. The first, from 1958 til 1970, was characterized by expropriation of large land holdings without changes in land use organization. The second period from 1970 til 1975 saw many pragmatic regulations brought about by the Baath regime, while the third period from 1975 til 1981 led to considerable changes in the agrarian structure based on the availability of large sums of money derived from the oil revenues. A large number of publications and documents are available about the first two periods, the developments during the third period however, are largely unknown until today. The following paper is therefore mainly concerned with these developments. Since about 1975 the government of Iraq has been able to under take expensive projects in the agricultural field. The revenue from the crude oil not only has permitted to pay for extensive reforms in land cultivation, it has also allowed to improve the living standard of the rural population through high investments in infrastructure and the payment of subsidies for consumer goods. To achieve this the population of many areas in northern Iraq has been resettled sometimes by force from their small villages into rural towns. The cultivation of the fields has been done through cooperatives aided by large state owned machine and tractor parks. Parallel to this development in the state and cooperative sector runs an interesting form of land use by private enterprise which is not only tolerated by the socialist Baath regime but also sup ported by it through favourable loans. Obviously the political leaders of Iraq have realized that generous support of private initiative will advance the economic development of the country more than central planning. This contributes to the general contentment and thus to the stabilisation of political power, and social mobility and diversity are being promoted.